Autonomous UAV 3D trajectory optimization and transmission scheduling for sensor data collection on uneven terrains - Andrey V. Savkin; Satish C. Verma; Wei Ni (Defence Technology, 2023)
This paper considers a time-constrained data collection problem from a network of ground sensors located on uneven terrain by an Unmanned Aerial Vehicle (UAV), a typical Unmanned Aerial System (UAS). The ground sensors harvest renewable energy and are equipped with batteries and data buffers. The ground sensor model takes into account sensor data buffer and battery limitations. An asymptotically globally optimal method of joint UAV 3D trajectory optimization and data transmission schedule is developed. The developed method maximizes the amount of data transmitted to the UAV without losses and too long delays and minimizes the propulsion energy of the UAV. The developed algorithm of optimal trajectory optimization and transmission scheduling is based on dynamic programming. Computer simulations demonstrate the effectiveness of the proposed algorithm.